DETERMINANT OF SUCCESFULL EXCLUSIVE BREASTFEEDING IN THE WORK AREA OF LANGSA LAMA PUSKESMAS LANGSA CITY - Rizka, Khairi; Gustiana, Gustiana; Juliastuti, Juliastuti (Journal of Midwifery and Community Health (JMCH), 2023)
Background : Breast milk is the best food for babies, therefore breats milk should be given to babies at least until the age 6 months and must be given until 2 years. Exclusive breastfeeding covereage in Langsa city in 2021 reaches the target of 80%, which is 83,8%. Various efforts carried out by the langsa city health center are classes for pregnant women and helath education about exclusive breastfeeding. Research Objectives: to determine the determinants of the success of exclusive breastfeeding in the working area of the Langsa public helath center Langsa city in 2022. The Research : This type of research is analytic with a cross sectional approach. The sampel in this study was 75 pregnant women. The research was carried out on 21-25 June 2022, the data analysis used was univariate and bivariate. The Results : The result showed that there was a relationship between helath education and exclusive breastfeeding wit a p value 0,002, with an OR 5.079, there is a relationship between the class of pregnant women and exclusive breastfeeding with a p value 0,002 with OR 5.464, there is a relationship between early intitation of breastfeeding exclusive breastfeeding with p value 0,009 with a OR of 3.949. Conclusion and suggestions : There is relationship between health education, class of pregnant women and early initittation of breastfeeding. It is hoped that further researches will be able to improve research on exclusive breastfeeding by adding variabel such as family support and cultural factor as wel the cohort method